1977
DOI: 10.1136/bmj.2.6097.1255
|View full text |Cite
|
Sign up to set email alerts
|

Acebutolol, atenolol, and propranolol and metabolic responses to acute hypoglycaemia in diabetics.

Abstract: SummaryIn a double-blind crossover study the symptomatic and metabolic effects of propranolol, acebutolol, and atenolol were studied during insulin-induced hypoglycaemia in diabetics treated with diet or hypoglycaemic tablets. All the drugs prevented tachycardia, but did not affect the other symptoms of hypoglycaemia. Propranolol delayed the recovery of the blood glucose concentration and impaired the secondary rise in the concentrations of blood lactate and non-esterified fatty acids in diet-treated diabetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(42 citation statements)
references
References 6 publications
0
42
0
Order By: Relevance
“…Both selective and non-selective P-adrenoceptor blockers have been reported to abolish the tachycardia in response to a low blood glucose in healthy volunteers (Deacon et al, 1977;Newman, 1976;Saunders et al, 1981) and patients with diabetes (Ostman et al, 1982). We found that after pre-treatment with propranolol LA, heart rate slowed during hypoglycaemia, probably due to reflex vagal activation in response to the rise in systolic and diastolic pressure.…”
Section: Resultsmentioning
confidence: 60%
“…Both selective and non-selective P-adrenoceptor blockers have been reported to abolish the tachycardia in response to a low blood glucose in healthy volunteers (Deacon et al, 1977;Newman, 1976;Saunders et al, 1981) and patients with diabetes (Ostman et al, 1982). We found that after pre-treatment with propranolol LA, heart rate slowed during hypoglycaemia, probably due to reflex vagal activation in response to the rise in systolic and diastolic pressure.…”
Section: Resultsmentioning
confidence: 60%
“…Impairment of glucose metabolism (Day, 1975;Waal-Manning, 1976), pronounced hypoglycaemia with masked symptoms (Barnett et al, 1980;Lohmann, 1980Lohmann, , 1981Lager et al, 1979;Waal-Manning, 1979;Deacon & Barnett, 1976) and decreased insulin secretion (Cerasi et al, 1972;Scandellari et al, 1978;Furman & Tayo, 1973;Holm et al, 1980;Harms et al, 1978) may result from Padrenoceptor blockade. While there is agreement that cardioselective P-adrenoceptor blocking agents should be preferred to unselective drugs in the treatment of diabetics (Kotler et al, 1966;Deacon et al, 1977;Abramson et al, 1966), there is no information with regard to the significance of intrinsic sympathomimetic activity in this respect. We have therefore compared the effects of pindolol (13' and 12-adrenoceptor blockade; marked intrinsic sympathomimetic activity [ISAJ; metoprolol (mainly Pladrenoceptor blockade; no ISA); and propranolol (,13 and 02-adrenoceptor blockade; no ISA); on hor-0306-5251/82/130407-11 $01.00 monal responses to insulin-induced hypoglycaemia in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons between non-selective betablocking agents, such as propranolol [25] , oxprenolol [92,93] and nadolol [92] and beta 1 -selective agents, such as atenolol [94,95] , metoprolol [96] and acebutolol [92,97,98] , have demonstrated close similarities in their blood pressure lowering characteristics. However, beta 1 -selective drugs may offer some advantages in hypertensive patients with concurrent conditions, such as obstructive airway disease, peripheral vascular disease and hyperlipidaemia [93] .…”
Section: Cardioselectivitymentioning
confidence: 99%
“…Glycogenolysis and glucose release from the liver are also partially mediated via beta 2 -receptor stimulation. For this reason, beta 1 -selective agents seem to be preferred in diabetic patients, especially if they are using insulin or oral antidiabetic drugs, because the beta 1 -selective drugs do not significantly delay recovery from hypoglycaemia [97,98] .…”
Section: Cardioselectivitymentioning
confidence: 99%